Nutrition Knowledge and the use of Nutrition Labels among Undergraduate Students in UiTM Puncak Alam - Khairul Ikram, Emmy Hainida; Nadhirah Ngah, Nur Amni; Khairul Ikram, Fazleen Emiza; Abu Hassan Shaari, Nur Suraiya (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2024)
This study aimed to determine the relationship between socio-demographic factors, nutrition knowledge, and the use of nutrition information labels during food purchases among undergraduate students in UiTM Puncak Alam. In this cross-sectional study, 156 undergraduate students between 18 and 25 years old were recruited from different locations in UiTM Puncak Alam. Data collection involved a self-report questionnaire with five sections covering sociodemographic and anthropometric information, nutrition knowledge level, use of food and nutrition labels, factors influencing label usage, and preferences for nutrition information formats. The Fisher’s Exact Test revealed no significant association between Body Mass Index (BMI) and nutrition knowledge or nutrition label usage (p>0.05). However, gender is significantly associated with nutrition knowledge (p<0.05). As for nutrition knowledge and nutrition label usage, there was no significant association between the level of nutrition knowledge and the use of nutrition labels during food purchases (p>0.05). To summarize, this research may determine the most recent data on general nutrition knowledge patterns among university students following the COVID-19 outbreak and underscores the importance of nutrition awareness in empowering students to make informed dietary choices, improving their health and well-being, necessitating targeted interventions and further research for a healthier, nutritionally aware generation.